Effects of Different Plant Density and Cutting Times on Yield of Stevia under the Çukurova Conditions - Leyla Sezer Tansı; Elnaz Samadpourrigani; Selin Gedik (International Journal of Secondary Metabolite)
Stevia (Stevia rebaudiana Bertoni) is perennial shrub form plant belonging to Asteraceae. It is indigenous to Paraguay and Brazil. Stevia is a natural sweetening and it has using potential to diets of obesity patients with non-caloric specialty and treatment of diabetes with insulin secretagogue specialty. In this study, the effects of different planting spaces and two cutting times on yields of two-year old Stevia plant were investigated. The highest dry leaf yield (515.96 kg/da) was obtained from blooming stage, cuttings in spring and 30x60 cm planting density.